Should local public employment services be merged with local social benefit administrations? - Christian Holzner; Sonja Munz (Journal for Labour Market Research, 2013)
The German Federal government has allowed local governments of some regions (Approved Local Providers) to be solely responsible for the care of unemployment benefit II recipients. In the remaining regions Joint Local Agencies were formed, where the local social benefit administrations work together with the local public employment services. We find that despite positive self-selection Approved Local Providers do not perform better than Joint Local Agencies. Even more interestingly, using a unique data set on organisational characteristics we are able to show that the organisational features implemented primarily by Approved Local Providers are positively correlated with the job finding probability of the unemployment benefits II recipients. Thus, local governments that self-selected into Approved Local Providers seem to have implemented a better organisational structure. However, their relatively poor performance overall compared to Joint Local Agencies suggests that they underestimated the benefits of having the local public employment service merged with the local social benefit administration.
Keywords: I38; J64; C31; 330; Optionskommune - Erfolgskontrolle; ARGE - Erfolgskontrolle; Beschäftigungseffekte; berufliche Reintegration; Langzeitarbeitslose; Experimentierklausel; Vermittlungserfolg; Arbeitsvermittlung; Hartz-Reform; Organisationsstruktur